Subgradients of the Value Function via Multiplier Sets of Parametric Convex Discrete Optimal Control Problems. (1st July 2021) - Toan, N. T.; Thuy, L. Q.
Abstract: This paper discusses differential stability of convex discrete optimal control problems with mixed constraints. Among the obtained results, we give formulas for exact computing the subdifferential and the singular subdifferential of the optimal value function via suitable multiplier sets.